Content validation of flood disaster preparedness action (FDPA) items among small and medium enterprises (SME) business - Hashim, Hajar Mariah; Ng, Yee Guan; Talib, Othman; Mohd Tamrin, Shamsul Bahri (Emerald Publishing Limited, 2019)
Purpose: This paper aims to present the process of construction and content validity of flood disaster preparedness action (FDPA) items to measure flood preparedness characteristics and activities among the small and medium enterprises (SME). Design/methodology/approach: The content validity process involved the act of conceptualization, development and validation. In short, it was implemented to develop the FDPA items that were used to measure flood preparedness at the SME level. The steps began with literature review (adopt and adapt) and judgment of expert panel on the item development process. The list of 54 items was developed. A panel of eight experts rated its content validation during a focus group discussion. Findings: In total, 52 items were acceptable to be passed on to the next stage of data collection. The items content validity (I-CVI) measurement of the items was within an acceptable range of more than 0.75, except for two items: Q38 and Q39. The scale content validity (S-CVI) value gave an excellent score of 0.95. Several items with low I-CVI score values for relevancy and clarity were subject to modification. Practical implications: Content validity ensured accurate interpretations of results. To support the construct validity of an instrument, documenting findings from content validity was essential. Originality/value: This paper demonstrated the initial phase of scale development on FDPA items. This newly developed item allows the integration of several flood disaster preparedness activities construct by review and judgment process by the panel of experts in the field.